KAJIAN TEORITIS: STRATEGI PENGEMBANGAN E- GOVERNMENT DALAM PELAYANAN ADMINISTRASI SECARA DARING - Widdy Yuspita Widiyaningrum (Universitas Pakuan, 2020)
ABSTRACT Development of e-government is an effort to develop governance based on (using) electronics in order to improve the quality of public services effectively and efficiently. Through e-government development, management systems and work processes are structured within the government by optimizing the use of technology information. The utilization of information technology includes 2 (two) related activities, namely: (1) data processing, information management, management systems and electronic work processes; (2) the use of advances in information technology so that public services can be accessed easily and cheaply by people in all regions of the country. The use of this technology is aimed at building effective and efficient governance by developing e-government in online administrative services so that in this way it will be easy and fast to the community by implementing services online. Online Population Administration Service, hereinafter referred to as Online Adminduk Service, is the process of managing population documents in which data / file requirements are sent using web-based electronic media by utilizing technology, communication and information facilities. Through the development of e-government in online administration services which is linked to the strategic concept of the SWOT analysis, including: Strengths (strengths), namely what strengths (goals) must be achieved so that technological progress will have an impact on optimal e-government development. Weaknesses (weaknesses), namely by avoiding wasted budget by planning and developing service sites so that there is transparency in the service. Opportunities (opportunities), which are supported by 4 (four) pillars of the e- government architecture framework, among others, access (optimal telecommunications networks), portals (integration with several agencies), information management and processing organizations (managing, providing, and processing information and electronic documents), as well as basic infrastructure and applications (supported by all infrastructure through hardware and software). And, the threats (threats), namely in the development of e-government in online administration services, it is necessary to consider that the higher the level of the site, the need for management system support, work processes, and information transactions between agencies which are increasingly complex as well. Keywords: SWOT analysis, E-Government, online administration services ABSTRAK Pengembangan e-government merupakan upaya untuk mengembangkan penyelenggaraan kepemerintahan yang berbasis (menggunakan) elektronik dalam rangka meningkatkan kualitas layanan publik secara efektif dan efisien. Melalui pengembangan e-government dilakukan penataan sistem manajemen dan proses kerja di lingkungan pemerintah dengan mengoptimasikan pemanfaatan teknologi informasi. Pemanfaatan teknologi informasi tersebut mencakup 2 (dua) aktivitas yang berkaitan yaitu: (1) pengolahan data, pengelolaan informasi, sistem manajemen dan proses kerja secara elektronis; (2) pemanfaatan kemajuan teknologi informasi agar pelayanan publik dapat diakses secara mudah dan murah oleh masyarakat di seluruh wilayah negara. Pemanfataan teknologi tersebut ditujukan untuk membangun tata kelola pemerintahan yangh efektif dan efisian dengan mengembangkan e-government pada pelayanan administrasi secara daring agar dengan caar ini akan dengan mudah dan cepat kepada masyarakat dengan menerapkan pelayanan secara daring. Pelayanan Administrasi Kependudukan Daring yang selanjutnya disebut Pelayanan Adminduk Daring adalah proses pengurusan dokumen kependudukan yang pengiriman data/berkas persyaratannya dilakukan dengan media elektronik yang berbasis web dengan memanfaatkan fasilitas teknologi, komunikasi dan informasi. Dengan melalui pengembangan e-government dalam pelayanan administrasi secara daring yang dikaikan dengan konsep strategi dari analisis SWOT, antara lain: Strenghts (kekuatan) yaitu kekuatan apa (sasaran) apa yang harus dicapai agar kemajuan teknologi akan berdampak pada pengembangan e-government yang optimal. Weaknesses (kelemahan) yaitu dengan menghindari pemborosan anggaran dengan perencanaan dan pengembangan situs pelayanan sehingga terjadi transparansi dalam pelayanan tersebut. Opportunities (peluang) yaitu dengan ditunjang dengan 4 (empat) pilar kerangka arsitektur e-government antara lain, akses (jaringan telekomunikasi yang optimal), portal (integrasi dengan beberapa instansi), organisasi pengelolaan dan pengolahan informasi (mengelola, menyediakan, dan mengolah informasi dan dokumen elektronik), serta Infrastruktur dan aplikasi dasar (didukung dengan semua prasarana melalui perangkat keras dan perangkat lunak). Dan, threats (ancaman) yaitu dalam Pengembangan e-government dalam pelayanan administrasi secara daring yaitu perlu dipertimbangkan bahwa semakin tinggi tingkatan situs tersebut, diperlukan dukungan sistem manajemen, proses kerja, dan transaksi informasi antar instansi yang semakin kompleks pula. Kata kunci: Analisis SWOT, E-Government, Pelayanan administrasi secara daring